Disability and other human questions - Goodley, Dan, 1972- (SocietyNow., 2021)
Goodley draws on decades of research to argue that disability has much to offer when we contemplate what it means to be human in the 21st Century. He addresses questions such as 'who's allowed to be human?'; 'are human beings dependent?'; and 'what does it mean to be human in the digital age?'